ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE, THE INFLUENCE OF THE JOB SATISFACTION, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, QUALITY OF WORK LIFE , AGAINST THE EMPLOYEEPERFORMANCE : A CASE STUDY : IN THE REGIONAL PUBLIC SERVICEWOMEN'S AND CHILDREN’ - Ahadi Arifin; Ibrahim Qomarius; Sullaida Sullaida; Nurmala Nurmala; Yenny Novita (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This aim of this study the organizational commitment as an intervening variable, the influence of the job satisfaction, Organizational Citizenship Behavior, Quality of Work Life, against the employee performance : Case Study : In The Regional Public Service Women's and Children's Hospital of Aceh Province . The research population is all employees of 254 people, and total sample of 156. The data analysis method used is Structural Equation Modelling. The results showed Organizational Commitment able to mediated the affect of the job satisfaction, organizational citizenship behavior and quality of work life against the employee performance is partially. And the relationship the job satisfaction, organizational citizenship behavior and quality of work life have a significant of relationship on the organizational commitment and employee performance.